Protective activity of coffee silverskin extracts: evaluation on erythrocyte oxidative-induced hemolysis - Ferreira da Vinha, Ana (2021)
Natural antioxidants from industry by-products have been receiving increasing attention, having in view the sustainability of the processes. Coffee silverskin, a pellicule that covers the raw coffee bean, is a by-product of coffee roasting since it is detached during this procedure. Human erythrocytes are particularly useful in the evaluation of the antioxidant properties of bioactive compounds, since they are susceptible to endogenous oxidative damage due to their specific role as oxygen carriers. The aim of this work was to evaluate the capacity of natural antioxidants of coffee silverskin to protect erythrocytes from oxidative injury induced by the water soluble radical initiator 2,2-azobis (2 amidinopropane)dihydrochloride (AAPH) and by H2O2. The results showed that coffee silverskin extracts protected erythrocytes in a significant way from oxidative-AAPH and oxidative-H2O2 induced hemolysis. As far as we know, there are no investigations, which evaluate the protective activity of coffee silverskin extracts on human erythrocytes hemolysis.